Вы находитесь на странице: 1из 22

Obj.

10 Inverse Functions
Unit 3 Rational Functions

Concepts & Objectives


Inverse Functions (Obj. #10) Review composition of functions Identify 1-1 functions Find the inverse of a 1-1 function

Composition of Functions
If f and g are functions, then the composite function, or composition, of g and f is defined by

(g

f )( x ) = g ( f ( x ) )

The domain of g f is the set of all numbers x in the domain of f such that f (x) is in the domain of g.

Composition of Functions
Example: Let f ( x ) = 2 x 1 and g ( x ) = a) Find ( f g )( 2) 4 g ( 2) = =4 21 b) Find ( g f )( 3) f ( 3) = 2( 3) 1 = 7 4 4 1 g ( 7 ) = = = 7 1 8 2 4 . x 1

(f

g )(2) = f ( g ( 2) ) = f ( 4 )
= 2( 4 ) 1 = 7

Composition of Functions
Example: Let f ( x ) = 2x 1 and g ( x ) = c) Write ( f g )( x ) as one function. 4 . x 1

(f

g )( x ) = f ( g ( x ) )

8 4 = 2 1 1 = x 1 x 1 8 x 1 8 x +1 = = x 1 x 1 x 1 9 x = x 1

One-to-One Functions
In a one-to-one function, each x-value corresponds to only one y-value, and each y-value corresponds to only one x-value. In a 1-1 function, neither the x nor the y can repeat. A function is a one-to-one function if, for elements a and b in the domain of f, ab implies f (a) f (b).

We can also say that f (a) = f (b) implies a = b.

One-to-One Functions
Example: Decide whether f ( x ) = 3x + 7 is one-to-one. We want to show that f (a) = f (b) implies that a = b:

f (a) = f (b ) 3a + 7 = 3b + 7 3a = 3b a=b Therefore, f is a one-to-one function.

One-to-One Functions
Example: Decide whether f ( x ) = x 2 + 2 is one-to-one. This time, we will try plugging in different values:
f (3) = 32 + 2 = 11

f ( 3) = ( 3) + 2 = 11 Although 3 3, f (3) does equal f (3). This means that the function is not one-to-one by the definition.

One-to-One Function
Another way to identify whether a function is one-to-one is to use the horizontal line test, which says that if any horizontal line intersects the graph of a function in more than one point, then the function is not one-to-one.

one-to-one

not one-to-one

Inverse Functions
Some pairs of one-to-one functions undo one another. For example, if
f ( x ) = 8x + 5

and

g( x ) =

x 5 8

then

f (10 ) = 8 (10 ) + 5 = 85

(for example)

85 5 80 g ( 85 ) = = = 10 8 8 This is true for any value of x. Therefore, f and g are called inverses of each other.

Inverse Functions
More formally: Let f be a one-to-one function. Then g is the inverse function of f if

(f
and

g )( x ) = x
f )( x ) = x

for every x in the domain of g, for every x in the domain of f.

(g

Inverse Functions
Example: Decide whether g is the inverse function of f .

f ( x ) = x3 1
f ( g( x )) =

g( x ) = 3 x + 1

x +1 1

= x +11 =x g ( f ( x )) = 3 x3 1 + 1 = 3 x3 =x

yes

Inverse Functions
If g is the inverse of a function f , then g is written as f -1 (read f inverse). In our previous example, for f ( x ) = x 3 1 ,
f 1 ( x ) = 3 x + 1

Finding Inverses
Since the domain of f is the range of f -1 and vice versa, if a set is one-to-one, then to find the inverse, we simply exchange the independent and dependent variables. Example: If the relation is one-to-one, find the inverse of the function.

F = {( 2,1) , ( 1,0) , ( 0,1) , (1,2) , ( 2,2)} G = {(3,1) , (0,2) , ( 2,3) , ( 4,0 )} G 1 = {(1,3) , (2,0) , (3,2) , ( 0,4 )}

not 1-1 1-1

Finding Inverses
In the same way we did the example, we can find the inverse of a function by interchanging the x and y variables. To find the equation of the inverse of y = f (x): Determine whether the function is one-to-one. Replace f (x) with y if necessary. Switch x and y. Solve for y. Replace y with f -1(x).

Finding Inverses
Example: Decide whether each equation defines a oneto-one function. If so, find the equation of the inverse. a) f ( x ) = 2x + 5 y = 2x + 5 x = 2y +5 2y = x 5 x 5 y= 2 1 5 1 f (x) = x 2 2 one-to-one replace f (x) with y interchange x and y solve for y

replace y with f -1(x)

Finding Inverses
Example: Decide whether each equation defines a oneto-one function. If so, find the equation of the inverse. b)
y = x2 + 2

not one-to-one

Finding Inverses
Alternative Method We can also use the definition to find the inverse: Set up the composition of f ( f 1 ( x ) ). By definition, this must equal x. Solve for f -1(x).

Finding Inverses
Example: Decide whether each equation defines a oneto-one function. If so, find the equation of the inverse. c) f ( x ) = ( x 2)
3 3 3

one-to-one
f(f

y = ( x 2)
3

x = ( y 2) x = y 2

y = 3 x +2
f 1 ( x ) = 3 x + 2

( x ) ) = ( f ( x ) 2) 3 1 x = ( f ( x ) 2) 3 x = f 1 ( x ) 2 f 1 ( x ) = 3 x + 2
1 1

Graphing Inverses
Back in Geometry, when we studied reflections, it turned out that the pattern for reflecting a figure across the line y = x was to swap the x- and y-values.

( x, y) ( y, x)
Therefore, if we were to graph our inverse functions, we would see that the inverse is the reflection of the original function across the line y = x.

Graphing Inverses
f ( x ) = 2x + 5 f ( x ) = ( x 2)
3

1 5 (x) = x 2 2

f 1 ( x ) = 3 x + 2

Homework
College Algebra Page 411: 3-21 (3s), 30-69 (3s) Homework: 42, 48, 57, 60a, 66a